Military Management in the Mid-Early Kingdoms of Viet People: Archaeology of Knowledge - Antonio Andrew Imanuel (Journal of International Conference Proceedings, 2022)
The constant military pressure and foreign threats over Viet people in the age of Imperial China, encourages researcher to find out how Viet people implemented military management. Researcher uses archaeology of knowledge as knife analysis to dig into the time of resistance against Ming Dynasty and Qin Dynasty. In military management, guerrilla warfare has been practiced at the time of Le Thai To in facing Ai Lao by stalking them from the mountains and forests of Thanh Hoa, and in facing Ming Dynasty, that the Viet guerrillas forced the Ming Dynasty troops to retreat. Guerrilla warfare also has been practiced as early as at the time of An Duong Vuong in facing Qin Dynasty, the Viet people were in the forest with animals, no one allowed themselves to be captured by the Qin army. Implementing of guerrilla warfare gave a fruitful result, the Viet people managed to killed General Do Thu and destroyed the Qin army. This research concludes that guerrilla warfare was used by Viet people as the main part of military management, specifically in facing constant military pressure and foreign threats. Such military management played a vital role in achieving important milestones in the history of Viet people.Â Keywords: Archaeology of knowledge, military management, guerrilla warfare, Viet.